(AuB)\C=(A\C) u (B\C) Prove or Disprove

(AuB)\C=(A\C) u (B\C) Prove or Disprove this statement.

This whole question turns on on simple principle in logic:
\(\displaystyle \left( {A \vee B} \right) \wedge \neg C \equiv \left( {A \wedge \neg C} \right) \vee \left( {B \wedge \neg C} \right)\).
 
(AuB)\C=(A\C) u (B\C) Prove or Disprove this statement.
The standard way to prove "set X= set Y" is to prove first "set X is a subset of set Y" and then "set Y is a subset of set X". The standard way to prove "set X is subset of set Y" is to start "if x is a member of set X" and then use the properties of sets A and B to conclude "then x is a member of set Y".

Here, "X" is \(\displaystyle (A\cup B)\ C\) so "if x is a member of \(\displaystyle (A\cup B)\C\) then x is in \(\displaystyle A\cup B\) but not in C. Since x is in \(\displaystyle A\cup B\) either x is in A or x is in B.

Either
1) x is in A but not in C so x is in A\C and so is in \(\displaystyle (A\C)\cup (B\C)\).

2) x is in B but not in C so x is in B\C and so is in \(\displaystyle (A\C)\cup (B\C)\)

In either case, \(\displaystyle (A\cup B)\C\) is a subset of \(\displaystyle (A\C)\cup (B\C)\).

Now, you need to do it the other way: if x is in \(\displaystyle (A\C)\cup (B\C)\) prove that x is in \(\displaystyle (A\ C)\cup (B\C)\).
 
Top